Niat dan Perilaku Penggunaan Mobile Wallet pada Mahasiswa Akuntansi - Amalo, Danio Kristan; Utama, I Made Karya (E-Jurnal Akuntansi; Vol 33 No 7 (2023)DO - 10.24843/EJA.2023.v33.i07.p19, 2023)
The Covid-19 pandemic has led to an increase in the use of mobile wallets. The aim of the study was to analyze the intention and behavior of using a mobile wallet using the UTAUT 2 model. The research was conducted on accounting students at the Faculty of Economics and Business, Udayana University. The sample was determined by the slovin formula and 92 people were found as the research sample. The research data was processed using multiple linear regression analysis. The results of the study show that performance expectations, social influence and price values have no effect on the intention to use a mobile wallet. Business expectations and hedonic motivation have a positive effect on the intention to use a mobile wallet. The test results also show that facilitating conditions do not affect the behavior of mobile wallet users. User habits and usage intentions have a positive effect on mobile wallet usage behavior. Keywords: Intention of Use; User Behavior; Mobile Wallets; UTAUT 2